2013
DOI: 10.1186/1471-2458-13-63
|View full text |Cite
|
Sign up to set email alerts
|

Community-level risk factors for notifiable gastrointestinal illness in the Northwest Territories, Canada, 1991-2008

Abstract: BackgroundEnteric pathogens are an important cause of illness, however, little is known about their community-level risk factors (e.g., socioeconomic, cultural and physical environmental conditions) in the Northwest Territories (NWT) of Canada. The objective of this study was to undertake ecological (group-level) analyses by combining two existing data sources to examine potential community-level risk factors for campylobacteriosis, giardiasis and salmonellosis, which are three notifiable (mandatory reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Chang et al (2009) previously identified a positive association between poverty levels and salmonellosis incidence rates at the county-level (Chang et al, 2009). More recently, in a Canadian study, Pardhan-Ali et al (2013) showed that rates of Salmonella infection were positively associated with the number of "households in core need" (homes that fall below defined standards and have low household incomes) (Pardhan-Ali et al, 2013). These findings may be influenced by a lack of safe food handling knowledge and behaviors among lowincome groups (Quinlan, 2013).…”
Section: Community Socioeconomic Factorsmentioning
confidence: 95%
“…Chang et al (2009) previously identified a positive association between poverty levels and salmonellosis incidence rates at the county-level (Chang et al, 2009). More recently, in a Canadian study, Pardhan-Ali et al (2013) showed that rates of Salmonella infection were positively associated with the number of "households in core need" (homes that fall below defined standards and have low household incomes) (Pardhan-Ali et al, 2013). These findings may be influenced by a lack of safe food handling knowledge and behaviors among lowincome groups (Quinlan, 2013).…”
Section: Community Socioeconomic Factorsmentioning
confidence: 95%
“…While research on the burden of AGI is burgeoning, there is still a limited understanding of enteric illness in subsets of populations, including populations who could be the most vulnerable to enteric illness [13][14][15][16]. For instance, although high-quality data are not currently available to accurately estimate the burden of AGI in Indigenous communities, research has documented environmental conditions that could increase the risk of AGI (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly important for Indigenous communities, who are often inadequately engaged in monitoring programmes [63][64][65]. Although public health monitoring is strong in many Circumpolar nations, 2 there is a continued need to adequately use Indigenous Knowledge in these programmes in a meaningful way; failure to do so has led to various gaps and challenges in coverage, data quality and relevance [4,[10][11][12]21,26,27,[29][30][31]65].…”
Section: Introductionmentioning
confidence: 99%